Transformation Of Islamic Da'wah Through Digital Content Training In Islamic Boarding Schools (Case Study at SMK YPC Cintawana, Tasikmalaya) - kiki Zakiah; Askurifai Baksin; Dian Widya Putri; Naditha Rizkya Hantoro (FAKULTAS DAKWAH UIN SALATIGA, 2025)
The transformation of Islamic da'wah through digital technology is an urgent need in the modern era. This study analyzes digital content training at SMK YPC Cintawana in improving the skills of students in the production and distribution of digital da'wah. With a qualitative approach to case studies, the results of this study show that this training improves students' abilities in videography, graphic design, copywriting, and digital communication strategies. Social media, YouTube, and podcasts help expand the reach of da'wah interactively. However, challenges such as cultural adaptation of Islamic boarding schools, limited infrastructure, and lack of understanding of digital communication strategies are still obstacles. Therefore, it is necessary to strengthen the digital curriculum, increase access to technology through external cooperation, and establish a pesantren media center. This strategy is expected to be able to make pesantren a modern da'wah center that still maintains Islamic values in the digital era.